Digital Maturity Level Analysis of the Regional Financial Management Information System for the Special Region of Jakarta Province - Nainggolan, Agus T.; Salomo, Roy Valiant (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Digital transformation is recognized as a key driver of change in public administration. Digital governance is a tool for building effective, inclusive, and accountable government in supporting the process of making government policies and providing services to the public. This research aims to analyze the current conditions and level of digital maturity of the DKI Jakarta Province Regional Financial Management Information System (SIPD). The research method used is qualitative with a descriptive approach. The data collection technique used was interviews with several key informants responsible for SIPD, namely Information Technology leaders, SIPD Conceptors, and SIPD users with indicators of strategy, leadership, development, user focus, and culture. The data analysis techniques used are data reduction, data presentation, and concluding. The research results show that the digital maturity level (DML) of the DKI Jakarta Province regional financial management information system is 4 categories at the early government level and 1 category is at the developing government level. The factor that obtained the highest results was the leadership factor which shows the digital awareness of stakeholders, but this digital awareness has not yet reached a sophisticated level. Apart from that, improvements are still needed regarding strategy, development, user focus, and digital culture factors.